The impact of human rights law on general international law - Kamminga, Menno T.; Scheinin, Martin (Oxford : Oxford University Press, 2009)
There is a growing discrepancy between the output of human rights courts which protect the individual and traditional international institutions which protect the interests of states. This volume provides a systematic analysis of the impact of international human rights courts on more traditional international institutions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights